(untitled) (Annals of Medical Research, 2021)
Aim: Our study aims to retrospectively evaluate the clinical, radiological and functional results of MIPO (minimally invasive plate osteosynthesis) in the treatment of tibial shaft and tibia distal 1/3 fractures.Material and Methods: Seventeen patients who underwent MIPO surgery due to tibial shaft and tibia distal 1/3 fractures between March 2011 – March 2015 were included in this study. Several parameters evaluated including radiological union, full-weight bearing, alignment problems, soft tissue complications, implant irritation, implant removal and AOFAS Score.Results: The most common fractures were noted as 42-A1, 42-B1 and 43-A1 according to AO/OTA Classification. The average follow-up period was 29.5 months (5-47 months). The average time for union was 4.7 months (2.5-10 months). The average period for full weight-bearing was 5.2 months (1-12 months). One patient (5.8%) had malunion (6 degrees of anterior angulation). Ten (58.8%) patients had complaints about medial sided ankle pain with wearing long boots. Three patients (17.6%) underwent implant removal. Average AOFAS score was 85.7 (63-100).Conclusion: MIPO is a safe and effective method for the tibial shaft and the tibia distal 1/3 region fractures regarding the high union rates, low complication incidence and good functional results.Keywords: Distal tibia fracture; MIPO; minimally invasive; biological fracture fixation; bone union.